2007
DOI: 10.1002/marc.200600900
|View full text |Cite
|
Sign up to set email alerts
|

Templated Synthesis of Composite Rings Using Core‐Shell Toroids

Abstract: In difference to compact objects of a similar size, toroidal structures have some distinguishing properties that originate from their open inner cavity and closed circuit. Here, a general facile methodology is developed to prepare composite rings with varied compositions on a large scale by using core‐shell toroids assembled from tri‐block copolymers of poly(4‐vinyl pyridine) (PVP)/polystyrene (PS)/PVP. Taking advantage of the complexation ability of the PVP shell, varied components that range from polymers, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…71 Since then a number of ABC, ABA and AB amphiphilic block copolymers have been observed to form toroidal micelles. [72][73][74][75][76][77][78][79][80][81] In all cases the toroidal micelles are essentially looped cylindrical micelles although their formation has been proposed to arise by different pathways. Wooley et al observed the formation of toroids from cylindrical and disk-like micelles through the elimination of high free energy end caps of cylindrical micelles or energetically unfavourable spherical micelles but also via the perforation of disc-like micelles 82 (Fig.…”
Section: Disk-like and Toroidal Micellesmentioning
confidence: 99%
“…71 Since then a number of ABC, ABA and AB amphiphilic block copolymers have been observed to form toroidal micelles. [72][73][74][75][76][77][78][79][80][81] In all cases the toroidal micelles are essentially looped cylindrical micelles although their formation has been proposed to arise by different pathways. Wooley et al observed the formation of toroids from cylindrical and disk-like micelles through the elimination of high free energy end caps of cylindrical micelles or energetically unfavourable spherical micelles but also via the perforation of disc-like micelles 82 (Fig.…”
Section: Disk-like and Toroidal Micellesmentioning
confidence: 99%
“…The stability of the toroidal structure is attractive in terms of further applications. For example, Wei et al27 used stable polymeric toroids as templates to prepare Au‐, ZnO‐, and ZnO/SiO 2 ‐polymer hollow composite rings. In that study, the RhB cores induced PL characteristics in the prepared toroids.…”
Section: Resultsmentioning
confidence: 99%
“…14C). 158 This acts as a general example for core-shell templating, the likes of which can be found using other core-shell structures, such as filomicelles and MPBs. [267][268][269][270][271] Pathways to controllably access metal nanorings may provide new materials with unique optical and superconducting properties.…”
Section: Toroidsmentioning
confidence: 94%